KAJIAN HERMENEUTIKA FRASA SELAMATKANLAH MEREKA DENGAN JALAN MERAMPAS MEREKA DARI API BERDASARKAN YUDAS 23a DAN IMPLEMENTASINYA DALAM KEHIDUPAN ORANG PERCAYA MASA KINI - Welsiana Wilkia; Silas Bandhaso Palalong (Misioner, 2021)
The problem discusses in Jude 23a is that there are different Bible translations and interpretations of the phrase, “save them by plundering them as if from fire”. This study aims to find the meaning of the phrase save them by depriving them of the fire based on Jude 23a and to find out how the meaning of the phrase is implemented in the lives of believers. The research method used is the hermeneutic method. The result of this research is the phrase, “save them by robbing them like from the fire” is not interpreted as something done with violence but a maximum and continuous effort to guide people who have fallen into heresies with love.